Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Pegawai Badan Pengawas Obat dan Makanan Di Batam - Hasanuddin; Evyanto, Winda (LPPM Universitas Putera Batam, 2022)
The purpose of the study was to determine the effect of leadership style and work environment on employee performance at the Food and Drug Supervisory Agency in Batam, using the saturated sample technique, in which all the population was sampled as many as 108 respondents who were employees of the Food and Drug Supervisory Agency in Batam. Batam. The method of data collection is a questionnaire. The data quality test in this study uses validity and reliability tests, classical assumption tests and influence tests in this study using multiple linear regression analysis and analysis of the coefficient of determination (R2), while hypothesis testing in this study uses (t test) and (F test) by using the software program SPSS 25. The coefficient of determination (R2) obtained from the variables of leadership style and work environment has an effect of 66.6% on employee performance. The results of multiple linear regression test show that leadership style (X1) has an effect of 22.9% on employee performance (Y) and work environment (X2) has an effect of 54.2% on employee performance (Y). From the results of the t test and F test, it can be concluded that leadership style has a partially significant effect on employee performance and the work environment has a partially significant effect on employee performance, and leadership style and work environment together have a significant simultaneous effect on employee performance at the Agency. Drug and Food Supervisor in Batam.